JAMES FENIMORE COOPER AND THE IDEA OF ENVIRONMENTAL CONSERVATION IN THE LEATHERSTOCKING TALES (1823-1841) - Ceisy Nita Wuntu (Universitas Gadjah Mada, 2014)
The spirit to respect the rights of all living environment in literature that was found in the 1970s in William Rueckert’s works was considered as the emergence of the new criticism in literature, ecocriticism, which brought the efforts to trace the spirit in works of literature. Works arose after the 1840s written by Ralph Waldo Emerson, Henry David Thoreau, and Margareth Fuller, the American transcendentalists, are considered to be the first works presenting the respect for the living environment as claimed by Peter Barry. James Fenimore Cooper’s reputation in American literary history appeared because of his role in leading American literature into its identity. Among his works, The Leatherstocking Tales mostly attracted European readers’ attention when he successfully applied American issues. The major issue in the work is the spirit of the immigrants to dominate flora, fauna and human beings as was experienced by the indigenous people. Applying ecocriticism theory in doing the analysis, it has been found that Cooper’s works particularly his The Leatherstocking Tales (1823-1841) present Cooper’s great concern for the sustainable life. He shows that compassion, respect, wisdom, and justice are the essential aspects in preserving nature that meet the main concern of ecocriticism and hence the works that preceded the transcendentalists’ work places themselves as the embryo of ecocriticism in America.